Financial optimization (Cambridge University Press, 1993)
The use of formal mathematical models and optimization in finance has become common practice in the 1980s and 1990s. This book clearly presents the exciting symbiosis between the fields of finance and management science/operations research. Prominent researchers present the state of the art in financial optimization, while analysts from industry discuss the latest business techniques practised by financial firms in New York, London and Tokyo. The book covers a wide range of topics: portfolio management of equities and fixed income investments, the pricing of complex insurance, mortgage and other asset-backed products, and models for risk-management and diversification.